Normal Aging does Not Impair Orbitofrontal-Dependent Reinforcer Devaluation Effects - Singh, Teghpal; Jones, Joshua L.; McDannald, Michael; Haney, Richard; Cerri, Domenic H.; Schoenbaum, Geoffrey (Frontiers in Aging Neuroscience, 2011)
Normal aging is associated with deficits in cognitive flexibility thought to depend on prefrontal regions such as the orbitofrontal cortex (OFC). Here, we used Pavlovian reinforcer devaluation to test whether normal aging might also affect the ability to use outcome expectancies to guide appropriate behavioral responding, which is also known to depend on the OFC. Both young and aged rats were trained to associate a 10-s conditioned stimulus (CS+) with delivery of a sucrose pellet. After training, half of the rats in each age group received the sucrose pellets paired with illness induced by LiCl injections; the remaining rats received sucrose and illness explicitly unpaired. Subsequently, responding to the CS+ was assessed in an extinction probe test. Although aged rats displayed lower responding levels overall, both young and aged rats conditioned to the CS+ and developed a conditioned taste aversion following reinforcer devaluation. Furthermore, during the extinction probe test, both young and aged rats spontaneously attenuated conditioned responding to the cue as a result of reinforcer devaluation. These data show that normal aging does not affect the ability to use expected outcome value to appropriately guide Pavlovian responding. This result indicates that deficits in cognitive flexibility are dissociable from other known functions of prefrontal – and particularly orbitofrontal – cortex.